Effect of augmented reality books in salivary cortisol levels in hospitalized pediatric patients: A randomized cross-over trial - Alarcón-Yaquetto D.E. (2021)
Objective: This study sought to assess the effect of reading augmented reality (AR) books on salivary cortisol levels in hospitalized pediatric patients compared to reading a standard children's book. Methods: This was a randomized, two-period, cross-over trial in hospitalized children aged 7–11 years. AR books currently in the market were used as intervention. Complete block randomization was used to randomize the order of the intervention. Children allocated to the ‘AR-first’ group received the book, a tablet and were left to interact independently with the technology for an hour. After a 48 -h wash-out period, children received a standard book. ‘Standard-book-first’ group received only the standard book and after wash-out received the tablet and the AR book. Salivary cortisol and a validated visual analogue scale (VAS) for psychological stress were assessed at the beginning and at the end of each intervention. Results: A total of 29 children were recruited in the study. One was lost during follow up. Cortisol levels decreased after the AR intervention (P = 0.019). Nevertheless, the decrease was not greater than the one associated to reading the standard book. VAS scores increased after the AR intervention (P < 0.001). Discussion: There is evidence of order and sequence effects that might explain results. First assessment of AR-based interventions on stress. Results justify further research. Conclusions: There was no evidence that reading AR books diminished cortisol levels more than reading a standard book. AR-books improved VAS score for psychological stress compared to a standard book. © 2021 Elsevier B.V.